Prevalence of addictive behaviours among adolescents from 73 low-and middle-income countries - De La Torre-Luque, Alejandro; Ozeylem, Fatos; Essau, Cecilia A. (Elsevier Ltd, 2021)
Introduction: Adolescence is a critical developmental stage for the initiation of substance use worldwide. However, the prevalence of various types of substances consumed by adolescents living in low- and middle- income countries (LMICs) across different continents is not fully understood. The aims of the present study were to estimate the prevalence of regular and problematic substance use among adolescents in 73 LMICs across different continents and to explore the role of country-specific factors on this prevalence. Method: Data of 314,187 adolescents (52.79% girls; median age = 15 years old) who participated in the Global School-based Student Health Survey (GSHS) were analysed. After estimating the weighted prevalence for each country, multilevel models were used to examine the influence of country-specific factors on the prevalence of substance use across 73 LMICs. Results: The results indicated that problematic alcohol use was more prevalent in LMICs with higher income levels. The prevalence of regular alcohol use was the highest in Zambia. Regular and problematic alcohol use was the least prevalent in Senegal and Myanmar. The findings also revealed that smoking and the consumption of marijuana and amphetamine were the most common among adolescents in Samoa, whereas the prevalences for these substances were the lowest in Laos. Conclusion: Economic wealth, religion and geographical factors seem to have a role in determining the prevalence of substance use among adolescents in LMICs. © 2021
Keywords: Adolescents; Country-specific risk factors; Global School-based Student Health Survey; Low-and middle-income countries; Substance use